Praktik Manajemen Sarana Dan Prasarana Dalam Kesiapan Uji Sertifikasi Kompetensi Siswa SMK Pelayaran Muhammadiyah Tuban - Choirul Huda; Suyanto .; A. Faizin (CV. ITTC INDONESIA, 2026)
Vocational education in vocational high schools (SMKs) requires adequate learning facilities and infrastructure to ensure that students are well prepared for competency certification examinations. However, many schools still face challenges in managing practical training facilities that have not yet fully met industry standards.This study aims to describe the practices of managing vocational learning facilities and infrastructure in preparing students’ readiness for competency certification examinations at SMK Pelayaran Muhammadiyah Tuban. This research employed a qualitative approach with a descriptive study design. The research subjects included the principal, the vice principal for facilities and infrastructure, and productive vocational teachers. Data were collected through in-depth interviews, observations, and document analysis. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results of the study indicate that the management practices of vocational learning facilities and infrastructure were implemented through planning facility needs based on the curriculum and certification standards, organizing the management of practical facilities, utilizing facilities according to scheduled learning activities, and maintaining practical facilities on a regular basis. These management practices contributed to students’ readiness, particularly in terms of practical skills mastery and mental preparedness in facing competency certification examinations. The findings conclude that well-planned and well-managed vocational learning facilities and infrastructure play an important role in enhancing students’ readiness for competency certification examinations.